Co-operative Learning Strategy and Academic Achievement of Business Studies Students in Secondary Schools in Wukari Education Zone, Taraba State, Nigeria - David, Ikpe Ijuo; Ruth, Magaji (MultiTech Publisher, 2024)
The study investigates the impact of cooperative learning strategies on the academic performance of Business Studies students in secondary schools in the Wukari Education Zone, Taraba State, Nigeria. It uses Levi's Social Interdependence Theory and Bandura's Social Learning Theory to support the research. The study used a quasi-experimental design and examined three instructional strategies: STAD Model, Jigsaw II Model, and Lecture methods. The study targeted 2,684 Business Studies students in 47 public secondary schools during the 2022/2023 academic session. The research instrument used was the Business Studies Achievement Test (BSAT), which was assessed by experts at Taraba State University. The instrument's internal consistency reliability was found to be 0.83.